PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI DI BANJARMASIN UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (Studi Kasus: PTS Dan PTN) - Ruslinda Agustina; Jamida Yuli (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research aims to determine the effect of economic motivation, career motivation, qualitymotivation and degree motivation to the interest of accounting students in Banjarmasin to follow PPAk. The method used in this research is a random sampling quota sampling. The unit of analysis is intended to be the respondent is a student majoring in accounting at STIENAS, STIE Indonesia, STIE Pancasetia, FEB UNLAM and the class of 2011 and 2012, with a total population of 565 students who meet the criteria and sample as many as 300 students. Hypothesis testing is done with the help of statistical software SPSS version 16. The results of this research indicate that economic motivation, quality motivation and degree motivation affect the interest of accounting students to follow PPAk.Contrary,career motivation does not affect the interest of accounting students to follow PPAk, because students argue to get a better career not only by following PPAk but also in other ways without having to follow PPAk. While simultaneously all the hypotheses affect the interest of accounting students to follow PPAk